2012
DOI: 10.4161/epi.21237
|View full text |Cite
|
Sign up to set email alerts
|

IDN2 has a role downstream of siRNA formation in RNA-directed DNA methylation

Abstract: In plants, a particular class of short interfering (si)RNAs can serve as a signal to induce cytosine methylation at homologous genomic regions. If the targeted DNA has promoter function, this RNA-directed DNA methylation (RdDM) can result in transcriptional gene silencing (TGS). RNA-directed transcriptional gene silencing (RdTGS) of transgenes provides a versatile system for the study of epigenetic gene regulation. We used transcription of a nopaline synthase promoter (ProNOS)-inverted repeat (IR) to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
1
33
1
1
Order By: Relevance
“…The hairpin RNA is processed redundantly by several DCL enzymes, including DCL3, into siRNAs of 21-24 nt (Dunoyer et al, 2005;Kanno et al, 2008;Daxinger et al, 2009). Transgene IRs are frequently used to silence genes at the transcriptional (Eamens et al, 2008;Kanno et al, 2008;Finke et al, 2012) and post-transcriptional levels (Dunoyer et al, 2005;Fusaro et al, 2006;Molnar et al, 2010). In Arabidopsis thaliana (Arabidopsis), several endogenous IRs that give rise to hairpin-derived siRNAs have been described (Henderson et al, 2006;Zhang et al, 2007;Dunoyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The hairpin RNA is processed redundantly by several DCL enzymes, including DCL3, into siRNAs of 21-24 nt (Dunoyer et al, 2005;Kanno et al, 2008;Daxinger et al, 2009). Transgene IRs are frequently used to silence genes at the transcriptional (Eamens et al, 2008;Kanno et al, 2008;Finke et al, 2012) and post-transcriptional levels (Dunoyer et al, 2005;Fusaro et al, 2006;Molnar et al, 2010). In Arabidopsis thaliana (Arabidopsis), several endogenous IRs that give rise to hairpin-derived siRNAs have been described (Henderson et al, 2006;Zhang et al, 2007;Dunoyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that 21–24-nt hairpin-derived siRNAs, which depend on Pol II transcription of inverted DNA repeats, can act in trans to trigger DNA methylation of unlinked homologous target sequences (Kanno et al 2005, 2008; Eamens et al 2008; Finke et al 2012; this study). It has not been clear, however, whether Pol IV/RDR2-dependent 24-nt siRNAs, which can induce methylation in cis at the site where they are generated (Lister et al 2008; Daxinger et al 2009), can similarly elicit RdDM in trans .…”
Section: Discussionmentioning
confidence: 62%
“…We performed a screen for ethyl methanesulfonate‐induced mutants ( no rna‐directed transcriptional silencing , nrd ) in which expression of a silenced reporter transgene is reactivated (Finke et al ., ). The line K/K ; H/H that was subjected to mutagenesis was doubly homozygous for a SILENCER ( H ) transgene on chromosome 4 containing an inverted repeat (IR) of the NOPALIN SYNTHASE promoter ( ProNOS ) sequence under the control of the CaMV 35S promoter ( Pro35 ) (Aufsatz et al ., ) and a TARGET transgene ( K ) ( K chr1–10 in Fischer et al ., ) on chromosome 1 containing a NEOMYCIN PHOSPHOTRANSFERASE II ( NPTII ) reporter gene conferring resistance to kanamycin and controlled by a ProNOS sequence (Figure a).…”
Section: Resultsmentioning
confidence: 97%